Phylogenomics resolves the etiology of dieback disease and deciphers Ceratocystis dalbergicans sp.nov., causal agent of Dalbergia sissoo decline - Haq, Imran Ul; Ijaz, Siddra; Latif, Muhammad Zunair; Khan, Iqrar Ahmad; Ali, Hayssam M.; Kaur, Sukhwinder (Frontiers in Genetics, 2023)
Dalbergia sissoo is one of the most economically important trees in forestry, agroforestry, and horticulture. Dieback is a serious threat to this tree species. The widespread dieback outbreaks and infestations have dras-tically killed billions of D. sissoo trees. Hence, we attempted to resolve the dieback etiology through phylo-genomics associated with D. sissoo mortality. Fungal isolates collected from dieback-affected tissues plants and investigated morphologically were explored as Ceratocystis species. Based on the symptomology, we have differentiated the dieback from Fusarium wilt and concluded that the species of Ceratocystis fimbriata sensu lato complex is causing shisham dieback in Pakistan. As the Ceratocystis species complex is a cryptic species complex, therefore, we went through genomics to the phylogenetic level for deciphering evolutionary hierarchy. Pathogen's operational taxonomy unlocked with the help of phylogenomics revealed that isolates from D. sissoo represent a species, distinct from other species in the C. fimbriata sensu lato species complex. The name Ceratocystis dalbergicans sp.nov. is provided for the fungus, causing dieback disease in D. sissoo.